Application and outcomes of a hybrid approach to chronic total occlusion percutaneous coronary intervention in a contemporary multicenter US registry. (1st November 2015) - Christopoulos, Georgios; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Yeh, Robert W.; Jaffer, Farouc A.; Wyman, R. Michael; Lombardi, William L.; Menon, Rohan V.; Grantham, J. Aaron; Kandzari, David E.; Lembo, Nicholas; Moses, Jeffrey W.; et al.
Abstract: Background: A hybrid approach to chronic total occlusion (CTO) percutaneous coronary intervention (PCI) prioritizing and combining all available crossing techniques was developed to optimize procedural efficacy, efficiency, and safety, but there is limited published data on its outcomes. Methods: We examined the procedural techniques and outcomes of 1036 consecutive CTO PCIs performed using a hybrid approach between 2012 and 2015 at 11 US centers. Results: Mean age was 65 ± 10 years and 86% of the patients were men, with a high prevalence of diabetes mellitus (43%) and prior coronary artery bypass graft surgery (34%). Most target CTOs were located in the right coronary artery (59%), followed by the left anterior descending artery (23%) and the circumflex (19%). Dual injection was used in 71%. Technical success was achieved in 91% and a major procedural complication occurred in 1.7% of cases. The final successful crossing technique was antegrade wire escalation in 46%, antegrade dissection/re-entry in 26%, and retrograde in 28%. The initial crossing strategy was successful in 58% of the lesions, whereas 39% required an additional approach. Overall, antegrade wire escalation was used in 71%, antegrade dissection/re-entry in 36%, and the retrograde approach in 42% of procedures. Median contrast volume, fluoroscopy time, and air kerma radiation dose were 260 (200–360) ml, 44 (27–72) min, and 3.4 (2.0–5.4) Gray, respectively. Conclusion: Application of a hybrid approach to CTO crossing resulted in high success and low complication rates across a varied group of operators and hospital practice structures, supporting its expanding use in CTO PCI.